HEALTH COMMUNICATION STRATEGY OF WONOGIRI REGENCY’S DPPKBP3A’S IN PURSUIT OF A STUNTING FREE WONOGIRI - Rifad Ibnubattuta; Arif Surya Kusuma (Universitas Muhammadiyah Jakarta, 2025)
Stunting is a serious public health problem because it impacts child growth and development and the quality of future human resources. Efforts to accelerate stunting reduction require effective communication strategies involving various parties. This study aims to analyze the communication strategy implemented by the Wonogiri Regency PPKBP3A Office in reducing stunting rates. The method used was descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results showed that the communication strategy was implemented through a collaborative approach involving interpersonal communication, educational media, and active community and cross-sector participation. This strategy reflects the integration of three community organizing models outlined by Rothman and Tropman: locality development, social planning, and social action. These models were realized through programs such as Foster Parents Overcoming Stunting (BAAS), Healthy Kitchen Overcoming Stunting (Dashat), and parent-to-toddler classes. The success of these programs was supported by local social structures, a culture of mutual cooperation, and the commitment of the local government. Meanwhile, this study also finds several obstacles of the implementation, such as sectoral egos, budget constraints, and a lack of human resource capacity. Overall, the findings suggest that a collaborative and community-base communication strategy serves as a constructive approach in reducing stunting rates and increasing public awareness of the importance of nutrition, health, and parenting.